The Analysis of Serum Vitamin D (25[OH]D) Level in Psoriasis Patients Comparing with Control Subjects - Ade Fernandes; Muhammad Yulianto Listiawan; Evy Ervianti; Trisniartami Setyaningrum (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Vitamin D has been shown to have an immunomodulatory effect, and previous studies have proven that vitamin D deficiency contributed to several autoimmune diseases, including psoriasis. Purpose: The purpose of this study was to determine serum vitamin D levels in psoriasis vulgaris patients and compare them with control subjects. Methods: The research samples were sixteen adults with psoriasis vulgaris and 16 control subjects. Blood samples were taken, and the serum 25 (OH) D levels were measured using the Chemiluminescent Microparticle Immunoassay method. Result: The mean serum vitamin D in psoriasis vulgaris patients and controls were 14.36 ± 6.36 and 19.92 ± 7.59 ng/mL, respectively. No psoriasis vulgaris were observed in patients with normal 25(OH)D levels, and only 3 control subjects with normal serum 25(OH)D levels. These results were not statistically significant (p = 0.09). Conclusion: Most patients with psoriasis vulgaris were observed having vitamin D deficiency. However, the prevalence of vitamin D deficiency in the control subjects was high as well. Therefore, there were no differences in serum 25(OH)D levels between psoriasis vulgaris and control patients.